The Legitimacy of Social Entrepreneurship: Reflexive Isomorphism in a Pre–Paradigmatic Field - Nicholls, Alex (Entrepreneurship Theory and Practice, 2010)
Following Kuhn, this article conceptualizes social entrepreneurship as a field of action in a pre–paradigmatic state that currently lacks an established epistemology. Using approaches from neo–institutional theory, this research focuses on the microstructures of legitimation that characterize the development of social entrepreneurship in terms of its key actors, discourses, and emerging narrative logics. This analysis suggests that the dominant discourses of social entrepreneurship represent legitimating material for resource–rich actors in a process of reflexive isomorphism. Returning to Kuhn, the article concludes by delineating a critical role for scholarly research on social entrepreneurship in terms of resolving conflicting discourses within its future paradigmatic development.
Keywords: Entrepreneuriat social; Isomorphisme; Réservé UdeM